已知函数f(-2x+1)=3x-2 则f(-3)=
1个回答
-2x+1=-3-2x=-3-1-2x=-4x=2
所以:
f(-3)=3×2-2=4
希望对你有帮助,满意请及时采纳,你的采纳是我回答的动力!
相关问题
已知函数f(3x)=(x-1)/(2+3x),则f(1)=____
已知函数f(x)=3x+2则f(-1)=
已知函数f(x)=(x+2)/(x+1)则f(1)+f(2)+f(3)+~+f(100)+f(1/2)+f(1/3)+~
已知f(x−1x)=x2+1x2,则函数f(3)=______.
已知f(x−1x)=x2+1x2,则函数f(3)=______.
已知函数f(x)=2x+1,x∈[1,5] 则f(2x-3)=_____;
已知函数f(x)=x^2/1+x^2则f(1)+f(2)+f(1/2)+f(3)+f(1/3)+f(4)+f(1/4)=
已知函数f(x)满足2f(x)+f(1/x)=3x(x>0),则函数f(x)=__
已知函数f(x)=x2+3x+1,则f(x+1)等于
已知函数f(x)满足f(x-1)=x,则f(x+1)= 已知函数f(x^2)=f(x)+2(x≥2)且f(2)=1,则f